DNA barcoding of Iranian leeches (Annelida: Clitellata: Hirudinida). (18th November 2021) - Darabi‐Darestani, Kaveh; Sari, Alireza; Khomenko, Andrii; Kvist, Sebastian; Utevsky, Serge
Abstract: The diversity of freshwater leeches (Clitellata; Hirudinida) of Iran was estimated by employing both DNA barcoding and species delimitation methods. Phylogenetic relationships of arhynchobdellid (including Hirudinidae, Praobdellidae, Haemopidae, and Erpobdellidae) and rhynchobdellid (Glossiphoniidae) leeches were reconstructed, based on the cytochrome c oxidase subunit I ( COI ) locus, using both new sequence data and those available from GenBank. Our results suggest that each of Helobdella stagnalis (Linnaeus, 1758), Glossiphonia concolor (Aphathy, 1888), Erpobdella borisi Cichocka & Bielecki, 2015, Dina lineata (O.F. Müller, 1774), Hirudo orientalis Utevsky and Trontelj, 2005, Haemopis sanguisuga (Linnaeus, 1758), Limnatis paluda (Tennent, 1859), and two unidentified species of Dina and Trocheta (these did not find species‐level matches in GenBank) are present in Iran. A potential case of phenotypic change in response to ecological adaptation was observed in E. borisi insofar as two genetically identical sub‐ and super‐terranean morphotypes were distinguished. The glossiphoniids of Iran and Europe are admixed in the phylogenetic tree, revealing low COI variation and no divergence within species between the continents for these taxa. Abstract : Maximum likelihood (ML) tree depicting phylogenetic relationships of some freshwater leech species from Iran using COI sequences. Bootstrap support values are given at nodes.